Maternal and child oral health interventions in Middle East and North Africa regions: a rapid review. (23rd July 2019) - Abuhaloob, Lamis; MacGillivray, Steve; Mossey, Peter; Freeman, Ruth
Abstract : Objectives: To conduct a rapid review to identify any maternal and/or child oral health interventions implemented and/or tested in Middle East and North Africa (MENA) countries generally, and Lebanon, Palestine and Syria specifically, and to compile information on the relative effectiveness of these interventions. Methods: A systematic search was conducted for primary and secondary literature indexed in five online databases, and the websites of the World Health Organisation (WHO), the International Union for Health Promotion and Education (IUHPE), the United Nations Children's Fund (UNICEF), United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA), and the United Nations Refugee Agency (UNHCR). Results: Two independent researchers reviewed 1, 180 records from the online databases, and 3, 120 reports from the WHO, UNRWA, UNICEF and UNHCR. Four unique studies were included and conducted in Syria, Saudi Arabia and Iran. No systematic reviews were found for targeted interventions in MENA regions. However, interventions using fluoridated toothpaste (Syria), preventive treatment and fluoridated chewing gum (Saudi Arabia), and oral health education with oral health reminders (Iran) were significantly effective in reducing early child caries (ECC) experience. In Syria and Iran, mother and child oral health promotions integrated into ongoing vaccination programmes were effective in reducing ECC. These interventions formed part of WHO and Ministry of Health programmes. Conclusion: Further investigation is essential to verify the effectiveness of incorporating multi‐disciplinary, theory‐driven oral health interventions into ongoing WHO maternal and child health programmes in MENA countries to assist in promoting oral health and wellbeing.